Chitosan performance during Paralytic Shellfish Toxins (PST) depuration of Mytilus chilensis exposed to Alexandrium catenella. (May 2021) - Tobke, Jésica; Giarratano, Erica; Ortiz, Alejandro; Garrido, Carla; Serra, Mariana; Gil, Mónica N.; Navarro, Jorge M.
Abstract: Blooms of the dinoflagellate Alexandrium catenella, which produces Paralytic Shellfish Toxins (PST), generate serious socio-economic consequences for mariculture in Chile, especially for the production of Mytilus chilensis and other bivalves. Palliative strategies, such as the depuration of mussels in enriched water with chitosan offer encouraging prospects against the advance of contaminated areas and toxin persistence. Adult mussels were fed with A. catenella for 20 days and then were allowed to depurate using chitosan as facilitator, for the same period. Intoxicated mussels showed a reduction in feeding activity and rapid PST accumulation in 20 days (C = 451.5t + 1, 673.6, R 2 = 0.55 p = 0.008). Not enough evidence was found to indicate a positive effect of chitosan in mussel depuration after 20 days (C = −311.1t + 8, 462.4, R 2 = 0.8 p = 0.001). At the end of the study, toxicity was higher than 800 μg STX eq kg −1 . C2 and GTX4 analogues were the most abundant in the dinoflagellate strain, while C2 and C1 were the most accumulated in mussels. The presence of C1 was notorious during depuration, as the persistence of GTX2, 3. GTX5 was only detected in A. catenella, while STX was only present in mussels. Mussel sensitivity to the presence of the toxic dinoflagellate was observed in the present study. The biotransformation, selective elimination and epimerization processes were deduced from intoxication and depuration experiments. Highlights: Chitosan was evaluated as chemical strategy to reduce depuration time of PST in mussel M. chilensis . Not enough evidence to state that chitosan facilitates toxin depuration after 20 days. Alexandrium catenella in diet reduced some physiological parameters of M. chilensis .